Racing cyclist power requirements in the 4000-m individual and team pursuits - Broker, J. P.; Kyle, C. R.; Burke, E. R. (Medicine & Science in Sports & Exercise, 1999)
Purpose: The purpose of this paper is: 1) to present field test data describing the power requirements of internationally competitive individual and team pursuiters, and 2) to develop a theoretical model for pursuit power based upon on these tests. Methods: In preparing U.S. cycling's pursuit team for the 1996 Atlanta Olympics, U.S. team scientists measured cycling power of seven subjects on the Atlanta track using a crank dynamometer (SRM) at speeds from 57 to 60 kph. By using these field data and other tests, mathematical models were devised which predict both individual and team pursuit performance. The field data indicate the power within a pace line at 60 kph averages 607 W in lead position (100%), 430 W in second position (70.8%), 389 W in third position (64.1%), and 389 W in fourth position (64.0%). A team member requires about 75% of the energy necessary for cyclists riding alone at the same speed. These results compare well with field measurements from a British pursuit team, to recent wind tunnel tests, and to earlier bicycle coast down tests. Results: The theoretical models predict performance with reasonable accuracy when the average power potential of an individual or team is known, or they may be used to estimate the power of pursuit competitors knowing race times. The model estimates that Christopher Boardman averaged about 520 W when setting his 1996, 4000-m individual pursuit record of 4 min 11.114 s and the Italian 4000-m pursuit team averaged about 480 W in setting their record of 4:00.958. Both used the "Superman" cycling position. Conclusions: These records would be very difficult to break using less aerodynamic riding positions, due to the extraordinarily high power requirements.